Thomas Jefferson the art of power - Meacham, Jon. (Newyork Random House, 2012)
n this magnificent biography, the Pulitzer Prize?winning author of American Lion and Franklin and Winston brings vividly to life an extraordinary man and his remarkable times. Thomas Jefferson: The Art of Power gives us Jefferson the politician and president, a great and complex human being forever engaged in the wars of his era. Philosophers think; politicians maneuver. Jefferson?s genius was that he was both and could do both, often simultaneously. Such is the art of power.
Keywords: Jefferson, Thomas, 1743-1826.